Perfectionism and Post-Secondary Students - Hayward, Lois; Arthur, Nancy (Canadian Journal of Counselling and Psychotherapy, 2007)
This study utilized a multidimensional approach to examine perfectionistic standards for academic achievement and their association with depression and anxiety. Post-secondary students completed the Multidimensional Perfectionism Scale, the Beck Depression Inventory, and the BeckAnxiety Inventory. Results revealed that both self-oriented and socially-prescribed perfectionism were associated with depression and anxiety, with socially-prescribed perfectionism most closely related to these symptoms of distress. Results confirm the multidimensional nature of perfectionism and the central importance of socially-prescribed perfectionism in predicting students' adjustment difficulties . Suggestions are discussed for counsellors to address issues of perfectionism related to students' goals for academic achievement.